Totalna piłka nożna i pomarańczowa tożsamość narodu holenderskiego - Melosik, Zbyszko (Wydawnictwo Naukowe UAM, 2016)
The article is devoted to analysis of relationship between Dutch way of playing soccer, so called “total” soccer and Dutch identity. The origin of total soccer is presented as well as its features with aggressive way of play and permanent exchange of players' position. The comparison of total soccer with architecture of Amsterdam as a total city is made. Also, the political context of soccer concerning the soccer games with Germany is considered.
Total Soccer and Orange Identity of Dutch Nation
Keywords: soccer; totality of play; Dutch identity; Dutch architecture; Dutch-German relationship